The Cost of Carbon Stored on Afforested Lands in the Southern United States - Madisen Fuller (Elsevier, 2021)
The Trillion Trees Campaign and Trillion Trees Initiative are part of the global climate change mitigation efforts to increase carbon storage on reforested and afforested lands. In this study, we estimated the cost of carbon stored on an acre of afforested loblolly pine (Pinus taeda) over a 100-years simulation period in the Lower Coastal Plain Region of the Southern United States. We varied site indices, interest rates, and carbon discount rates for ascertaining the impacts on the cost of the total carbon stored across three carbon pools (stand, finished wood products, and wood present in landfills). After accounting for the net profits from an acre of afforested loblolly pine plantation, the cost of stored carbon currently ranges between $0.76/ton and -$10.12/ton over a 100-years simulation period with zero carbon discount rate. The cost of stored carbon is lower for higher site indices. The cost of stored carbon decreases with a rise in the carbon discount rate. Afforestation is a cost-effective nature-based solution for mitigating climate change. It should be considered as a potential strategy for reducing the overall cost of mitigating climate change in the United States. The findings of the study are relevant for efforts promoting afforestation as a tool for mitigating climate change worldwide.